A rare combination of cardiovascular anomaly: Aortic stenosis at sinotubular junction level and discontinuity of right coronary artery. Issue 4 (23rd January 2022) - Ling, Yunfei; Song, Jiayi; Li, Tiange; Lin, Ke
Abstract: Background: Supravalvular aortic stenosis (SVAS) and congenital discontinuity of right coronary artery are both rare congenital cardiovascular abnormalities. This is the first case report about SVAS that occurred with the congenital discontinuity of right coronary artery. Materials & Methods: A 3‐month‐old female infant presented with aortic stenosis at sinotubular level and congenital right coronary artery deficiency. According to cardiovascular CT results, Doty technique was adopted to restore the aortic root geometry under cardiopulmonary bypass. An angioplasty was performed to establish right coronary blood flow at the same time. The patient had no abnormal cardiac symptoms after surgery. The postoperative echocardiogram revealed a normal laminar flow of the right coronary artery into the right coronary sinus, normal aortic blood flow and normal myocardial functions. Discussion: SVAS is characterized by the stenosis of the lumen of the ascending aorta above the aortic valve. Congenital discontinuity of RCA is probably related to dysplasia or congenital occlusion of the RCA during the development of embryo. This kind of malformation may lead to the deficiency of blood supply in sinoatrial and atrioventricular node, eventually causing their dysfunction, which usually leads to arrhythmias as the main manifestations. Angioplasty can improve blood supply of the heart without increasing the risk of major complications, and perioperative prognosis revealed good. This case image also suggested that cardiovascular CT can provide excellent visualization of complex vascular anatomies. Conclusions: We reported this rare combination of malformations consisted of SVAS and discontinuity of right coronary artery. We treated this patient with the Doty technique and angioplasty procedures.